2019
DOI: 10.3390/foods8070231
|View full text |Cite
|
Sign up to set email alerts
|

Use of Attenuated Total Reflectance—Fourier Transform Infrared (ATR-FTIR) Spectroscopy in Combination with Multivariate Methods for the Rapid Determination of the Adulteration of Grape, Carob and Mulberry Pekmez

Abstract: Pekmez, a traditional Turkish food generally produced by concentration of fruit juices, is subjected to fraudulent activities like many other foodstuffs. This study reports the use of Fourier transform infrared spectroscopy (FTIR) in combination with chemometric methods for the detection of fraudulent addition of glucose syrup to traditional grape, carob and mulberry pekmez. FTIR spectra of samples were taken in mid-infrared (MIR) range of 400–4000 cm−1 using attenuated total reflectance (ATR) sample accessory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 27 publications
3
13
0
Order By: Relevance
“…(2010) who reported that glucose has absorption bands at 902 cm −1 , 1,032 cm −1 , 1,036 cm −1 , the most important of which being at 1,032 cm −1 . In the same context, the peak observed at 1,040 cm −1 is also close to that of glucose, reported at 1,027 cm −1 by Yaman and Velioglu (2019). It is also worth noting that the work of Se et al.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…(2010) who reported that glucose has absorption bands at 902 cm −1 , 1,032 cm −1 , 1,036 cm −1 , the most important of which being at 1,032 cm −1 . In the same context, the peak observed at 1,040 cm −1 is also close to that of glucose, reported at 1,027 cm −1 by Yaman and Velioglu (2019). It is also worth noting that the work of Se et al.…”
Section: Resultssupporting
confidence: 86%
“…The results obtained are in conformity with the findings of Sun (2009) as well as Dasa et al (2017), who reported that carbohydrates have an absorption region that extends between 700 and 950 cm −1 and of Wang et al (2010) who reported that glucose has absorption bands at 902 cm −1 , 1,032 cm −1 , 1,036 cm −1 , the most important of which being at 1,032 cm −1 . In the same context, the peak observed at 1,040 cm −1 is also close to that of glucose, reported at 1,027 cm −1 by Yaman and Velioglu (2019). It is also worth noting that the work of Se et al (2018) and Mellado-Mojica et al ( 2016) report a maximum glucose uptake in the vicinity of 1,022 and 1,029 cm −1 (Table 3).…”
Section: Detection Of Glucose Adulteration By Nir and Mirsupporting
confidence: 79%
“…The standards of phenolic compounds, organic acids and individual carbohydrates were determined based on the retention times and quantified based on their calibration curves (all the curves had R 2 higher than 0.98). For samples, the limits of detection (LOD) and limits of quantification (LOQ) were calculated according to Kuppusamy et al (2018) [36][37][38].…”
Section: Hplc Instrumentation and Separation Conditionsmentioning
confidence: 99%
“…However, the PLS model assumes a supervised learning process instead of an unsupervised learning approach in the PCA model ( Yang and Yang, 2003 ). The application of FTIR spectroscopy and HPLC combined with multivariate calibration for analysis was reported over several biological raw materials, showing a very significant prediction accuracy, such as honey ( Anjos et al, 2015 ; Tahir et al, 2017 ), virgin olive oil ( Hirri et al, 2016 ), Mangosteen ( Tejamukti et al, 2020 ), grape, carob and mulberry ( Yaman and Velioglu, 2019 ), coffee beans ( Liang et al, 2016 ), salvia seeds ( Tulukcu et al, 2019 ), and kakadu plum powders ( Cozzolino et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%